Lessons learned from an unusual case of severe hypoglycemia. Issue 2 (March 2019) - Improta, M.R.; Strollo, F.; Gentile, S.; ,
Abstract: We are hereby reporting on a woman with type 1 diabetes getting insulin, 4 shots a day, and referring to us for an episode of severe hypoglycemia occurred after vigorously rubbing a lipo-hypertrophy (LH). She had always injected insulin into an abdominal LH area but had never suffered from any hypoglycemic event (Hypo) during the last period. Nevertheless her history included frequent Hypos, mostly mild-to-moderate but sometimes severe and eventually ending into unconsciousness and her glycemic control was poor (HbA1c 8.3%, mean FPG 161 ± 22 mg/dl, mean PPG 218 ± 51 mg/dl, glycemic variability (106 ± 44 mg/dl). In fact, all of a sudden she rubbed vigorously the LH area trying to get rid of the abdominal skin thickening and soon after a severe Hypo occurred causing her to need for emergency medical assistance. When back at home, she corrected her technique and carefully refrained from inject insulin into the LH so that after six months the lesion disappeared, glycemic control improved and no Hypo occurred any more. Based on the recent publication reporting on a woman with a large LH consisting of thickened skin surrounding some fluid containing insulin at concentrations 13 fold those in blood, we hypothesize that such severe depended on massive insulin release from rubbed skin stores into the blood stream.